Normal haematological values of Galla goats in Kenya - Wesonga, H.O.; Nandokha, E. (1989)
Haematological values of healthy Galla goats have been determined. These values have been found to differ from those reported by other authors in different breeds of goats from various countries. Those values found to be of highly significant difference (P